Discovery of Novel Pyrimidine Based Small Molecule Inhibitors as VEGFR-2 Inhibitors: Design, Synthesis, and Anti-cancer Studies - Dhawale, Sachin A.; Mokale, Santosh N.; Dabhade, Pratap S. (Current Computer - Aided Drug Design, 2025)
BackgroundReceptor tyrosine kinases (RTKs) are potent oncoproteins in cancer that, when mutated or overexpressed, can cause uncontrolled growth of cells, angiogenesis, and metastasis, making them significant targets for cancer treatment. Vascular endothelial growth factor receptor 2 (VEGFR2), is a tyrosine kinase receptor that is produced in endothelial cells and is the most crucial regulator of angiogenic factors involved in tumor angiogenesis. So, a series of new substituted N-(4-((2-aminopyrimidin-5-yl)oxy)phenyl)-N-phenyl cyclopropane-1,1-dicarboxamide derivatives as VEGFR-2 inhibitors have been designed and synthesized.MethodsUtilizing H-NMR, C13-NMR, and mass spectroscopy, the proposed derivatives were produced and assessed. HT-29 and COLO-205 cell lines were used for the cytotoxicity tests. The effective compound was investigated further for the Vegfr-2 kinase inhibition assay, cell cycle arrest, and apoptosis. A molecular docking examination was also carried out with the Maestro-12.5v of Schrodinger.ResultsIn comparison to the reference drug Cabozantinib (IC50 = 9.10 and 10.66 μM), compound SP2 revealed promising cytotoxic activity (IC50 = 4.07 and 4.98 μM) against HT-29 and COLO-205, respectively. The synthesized compound SP2 showed VEGFR-2 kinase inhibition activity with (IC50 = 6.82 μM) against the reference drug, Cabozantinib (IC50 = 0.045 μM). Moreover, compound SP2 strongly induced apoptosis by arresting the cell cycle in the G1 phase. The new compounds' potent VEGFR-2 inhibitory effect was noted with key amino acids Asp1044, and Glu883, and the hydrophobic interaction was also observed in the pocket of the VEGFR-2 active site by using a docking study.ConclusionThe results demonstrate that at the cellular and enzyme levels, the synthetic compounds SP2 are similarly effective as cabozantinib. The cell cycle and apoptosis data demonstrate the effectiveness of the suggested compounds. Based on the findings of docking studies, cytotoxic effects, in vitro VEGFR-2 inhibition, apoptosis, and cell cycle arrest, this research has given us identical or more effective VEGFR-2 inhibitors.
Keywords: molecular modeling